A highly asynchronous developmental program triggered during germination of dormant akinetes of filamentous diazotrophic cyanobacteria. Issue 1 (6th December 2017) - Perez, Rebeca; Wörmer, Lars; Sass, Peter; Maldener, Iris
Abstract: Germination of akinetes of filamentous heterocyst-forming cyanobacteria of the order Nostocales is an essential process that ensures survival and recolonization after long periods of unfavorable conditions, as desiccation, cold and low light. We studied the morphological, physiological and metabolic changes that occur during germination of akinetes in two model species of cell differentiation, Anabaena variabilis ATCC 29413 and Nostoc punctiforme ATCC 29133, which live in different habitats. We characterized the akinete envelopes and showed their similarity to envelopes of N2 -fixing heterocysts. Akinete germination started inside the envelopes and was dependent on light intensity but independent of nitrogen supply. During the germination of A. variabilis akinetes, cell division and heterocyst differentiation were highly accelerated. The energy for cell division was initially supplied by respiration of glycogen and subsequently by photosynthesis. By contrast, during germination of N. punctiforme akinetes, cell division and heterocyst differentiation were slow. During the initial 15–20 h, N. punctiforme akinetes increased in volume and some burst. Only then did intact akinetes start to divide and fully germinate, possibly fueled by nutrients released from dead akinetes. The different strategies used by these different cyanobacteria allow successful germination of dormant cells and recolonization under favorable conditions. Abstract : Different filamentous cyanobacteria use different germination strategies of akinetes, which are spore-like resistant cells, as an important step in the life cycle allowing recovery from dormancy after change of environmental conditions.